An open-source low-cost TDOA-based sound source localization system - Mahmoud A. Alnaanah; Amir Abu Al-Aish; Mohd H.S. Alrashdan; Mohammad Zayed Ahmed; Haitham A. Alasha'ary; Hamzah Hmeidi (Bulletin of Electrical Engineering and Informatics, 2026)
Sound source localization (SSL) has many civilian and military applications, such as robotics, gunshot localization in nature reserves and warfare, surveillance, wild animal tracking, and rescue missions. One effective method of SSL is measuring the time difference of arrival (TDOA) for an array of microphones. The TDOA method requires designated hardware that is quite expensive and might require specific proprietary software; this makes SSL research expensive and difficult to develop software for, especially for hobbyists and educators. This paper presents a low-cost and easy-to-build SSL system that is built using 4 USB sound cards along with 4 microphones and a USB hub. The code for the system is made open for the public, and it is based on open-source applications, which are Linux, GStreamer, and Octave, to provide an open environment for studying and researching SSL. The localization process relies on finding the TDOA using generalized cross correlation (GCC) thresholding and finding the intersection point of three two-sheeted hyperboloids. The theoretical and experimental descriptions of the system are presented in this paper, along with some of the challenges, such as the microphones’ timing and position calibration. Despite the low sampling rate and high noise of the used USB sound cards, the system was able to locate the sounds within a 2.4 m radius with a root mean square error (RMSE) of 7.23% and a mean error of 6.12%.